PROFIL AKTIVITAS ANAK JALANAN DI JALAN HARAPAN RAYA - Ridho Julianto; Rosmawati Rosmawati; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to find out the activity profile of street children. This type of research is research using a qualitative approach and analyzed descriptively to obtain information. The informant in this study is a street child who is on Jalan Harapan Raya Kota Pekanbaru, numbering 3 people. This study uses data retrieval techniques, namely, interviews and observations. Samples in qualitative research are named as sources or informants. The informant in this study is a street child who is on Harapan Raya road, Pekanbaru numbering 3 children consisting of 3 girls. Taken using a sampling technique, purposive sampling. The results showed that street children on Harapan Raya street are included in the Type of Children on the street. Street children's activities are divided into two, namely, physical and non-physical. Physical activities of street children such as cleaning the house, helping parents, playing, and working on the streets by selling newspapers. While non-physical activity is closely related to the way street children think, study at school and at home, pray in the mosque and the feelings they experience.Key Words: Profile, Activity, Street Children.